Fungemia and Other Fungal Infections Associated with Use of Saccharomyces boulardii Probiotic Supplements - Rannikko Juha; Holmberg Ville; Karppelin Matti; Arvola Pertti; Huttunen Reetta; Mattila Eero; Kerttula Niina; Puhto Teija; Tamm Ülle; Koivula Irma; Vuento Risto; Syrjänen Jaana; et al. (Center for Disease Control and Prevention, 2022)
Because of widespread use of probiotics, their safety must be guaranteed. We assessed use of Saccharomyces boulardii probiotic yeast from medical records for patients who had Saccharomyces fungemia or other clinical Saccharomyces culture findings. We evaluated all Saccharomyces sp. findings at 5 university hospitals in Finland during 2009–2018. We found 46 patients who had Saccharomyces fungemia; at least 20 (43%) were using S. boulardii probiotic. Compared with a control group that had bacteremia or candidemia, the odds ratio for use of an S. boulardii probiotic was 14 (95% CI 4–44). Of 1,153 nonblood culture findings, the history for 125 patients was checked; at least 24 (19%) were using the probiotic (odds ratio 10, 95% CI 3–32). This study adds to published fungemia cases linked to use of S. boulardii probiotic and sheds light on the scale of nonblood Saccharomyces culture findings that are also linked to use of this probiotic.